2022
DOI: 10.3349/ymj.2022.63.s14
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of the Literature on Smart Healthcare for Older Adults

Abstract: Smart healthcare systems are being designed to provide medical services to and improve the daily lives of older adults. However, most research has been focused on technical issues, despite a need to conduct in-depth studies on related ethical issues. Therefore, this study aimed to examine ethical issues in smart healthcare for older adults. We reviewed published literature using PubMed. In total, 292 documents were analyzed by applying the scoping review method. Finally, 29 articles were selected from the 292 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Haase et al 7 also identified a general disinterest and lack of knowledge of computers among older adults to be a barrier to the use of Internet-based services. This finding aligns with a recent scoping review 8 that identified a reduced responsiveness to technological changes among older adults. This is an important consideration for Internet-based services targeting older adults, as they may initially require more support and time to become comfortable and efficient users of any new technology and subsequently gain maximum benefit.…”
Section: Discussionsupporting
confidence: 91%
“…Haase et al 7 also identified a general disinterest and lack of knowledge of computers among older adults to be a barrier to the use of Internet-based services. This finding aligns with a recent scoping review 8 that identified a reduced responsiveness to technological changes among older adults. This is an important consideration for Internet-based services targeting older adults, as they may initially require more support and time to become comfortable and efficient users of any new technology and subsequently gain maximum benefit.…”
Section: Discussionsupporting
confidence: 91%
“…In the evaluation of competence service quality, all ve dimensions fall into quadrants and with good evaluation,bur the lowest score in the capability dimension is "timely technical assistance", which indicates that some patients encounter technical di culties during the consultation process and lack medical staff's assistance. The reason for this is that some middle-aged and elderly people face a technological gap [27], poor vision and hearing [28], and low ability to adapt to new technologies, which makes it di cult to use smart devices and aggravates the di culty of accessing medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults are often willing to accept some privacy infringements in favour of the safety and other benefits provided [ 3 ], but despite this trade-off, they still require technology to be reliable and trustworthy [ 36 ]. Sometimes the promise of safety could lead elders to accept technologies before actually being ready and making compromises which do not benefit their wellbeing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, life expectancy has increased considerably, especially in developed countries [ 1 ]. Consequently, the rate of population aging is progressing rapidly and, as the portion of people over 65 years of age continues to grow, demographic aging becomes one of the most serious challenges that health and social systems worldwide have to face [ 2 , 3 ]. Traditional care models are struggling to meet the needs of this rapidly aging global population: there is a growing demand of healthcare services, a shortage of healthcare professionals and a huge burden is imposed on informal caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation